Effects of Scaling Up Private School Choice Programs on Public School Students - David N. Figlio; Cassandra M.D. Hart; Krzysztof Karbownik (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Using a rich dataset that merges student-level school records with birth records, and leveraging a student fixed effects design, we explore how the massive scale-up of a Florida private school choice program affected public school students' outcomes. Program expansion modestly benefited students (through higher standardized test scores and lower absenteeism and suspension rates) attending public schools closer to more pre-program private school options. Effects are particularly pronounced for lower-income students, but results are positive for more affluent students as well. Local and district-wide private school competition are both independently related to student outcomes.
Keywords: H75; I21; I22; I28; 330; school choice; school competition; externalities; student achievement; behavioural outcomes